2010
DOI: 10.1007/s11250-010-9751-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in circulating levels of plasma interleukin-8 during peripartum period in Murrah buffaloes (Bubalus bubalis) under subtropical climate

Abstract: The objective of this study was to elucidate the changes in circulating levels of plasma interleukin-8 (IL-8) during peripartum period in Murrah buffaloes (Bubalus bubalis). IL-8 was estimated in blood plasma of healthy peripartum Murrah buffaloes (n=6) on days ± 30, ± 15, ± 5, ± 3, ± 1 and 0 pre- and postpartum with respect to the day of parturition (day 0) in each of the two different seasons (hot-humid and spring). The mean microclimate Temperature-Humidity Index (THI) during spring season was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The author concluded that the increased serum IL-6 and IL-8 levels in infected buffaloes suggest that these cytokines may play a role in the immune reaction during liver fluke infection in some species. Kumar et al (2011) examined IL-8 levels in Murrah buffaloes during the peripartum period and reported that IL-8 was high in the postpartum period. They explained that the rise in IL-8 levels in buffaloes is a cumulative immune response not only to the physiological stress of parturition and uterine involution during the postpartum period, but also to the high thermal stress from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that the increased serum IL-6 and IL-8 levels in infected buffaloes suggest that these cytokines may play a role in the immune reaction during liver fluke infection in some species. Kumar et al (2011) examined IL-8 levels in Murrah buffaloes during the peripartum period and reported that IL-8 was high in the postpartum period. They explained that the rise in IL-8 levels in buffaloes is a cumulative immune response not only to the physiological stress of parturition and uterine involution during the postpartum period, but also to the high thermal stress from the environment.…”
Section: Discussionmentioning
confidence: 99%